(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
There are at least three kinds of that one encounters in Kanthapura: social, political and religious. Out of these the religious ones are presented as most centrally associated with social regeneration in the village Kanthapura. This is consonant without the true tradition in India, where social reformers have invariably been profoundly religious men. Again, the idea of social regeneration is linked up with rituals like the Harikatha. Raja Rao’s protagonist Moorthy knows very well that the real key to the rustic Indian mind is religion.